2018
DOI: 10.1177/1464420718766626
|View full text |Cite
|
Sign up to set email alerts
|

Interlaminar adhesion assessment of carbon-epoxy laminates under salt water ageing using peel tests

Abstract: The aim of this study is to assess the interlaminar adhesion of carbon-epoxy laminates under salt water condition. Carbon-epoxy laminate specimens were immersed in a salt water tank for 60 days. Some specimens were then dried at room temperature for 280 days, until recovering their initial weight. Specimens were tested using the composite peel test, an adaptation of the floating roller peel tests for composite materials. The results showed a degradation of peel strength in some areas due to the ageing process.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…The peel strength data received for mild steel and copper indicated that the addition of modified GO (GO-KF) enhanced the peel strength of the epoxy coating. 39 This proved that modified GO acts as a good reinforcing agent. The corrosion protection mechanism of epoxy coating without any reinforcing agent is simple.…”
Section: Peel-off Testmentioning
confidence: 85%
“…The peel strength data received for mild steel and copper indicated that the addition of modified GO (GO-KF) enhanced the peel strength of the epoxy coating. 39 This proved that modified GO acts as a good reinforcing agent. The corrosion protection mechanism of epoxy coating without any reinforcing agent is simple.…”
Section: Peel-off Testmentioning
confidence: 85%
“…Peel strength value of the GO-BD/epoxy coating was found to be 1.478N. The strength of GO-BD/ epoxy composite coating was better than the neat epoxy and epoxy treated with GOcoating 40 . This showed that GO-BD increased the strength of the coating.…”
Section: Peel Test Measurementsmentioning
confidence: 89%
“…However, the forces for the PA-PA interface dropped suddenly after 20 mm displacement. The average peel loads were determined along 100 mm peeling lengths ranging from 20 mm to 120 mm, discarding the first 20 mm displacement (except for the PA-PA interface) [34,35]. According to this method, as seen in Fig.…”
Section: Interfacial Strengthmentioning
confidence: 99%